Evaluation of potential-induced degradation in crystalline Si solar cells using Na fault injection. (September 2016) - Oh, Wonwook; Kim, Junhee; Kang, Byungjun; Bae, Soohyun; Lee, Kyung Dong; Lee, Hae-Seok; Kim, Donghwan; Chan, Sung-Il
Abstract: Photovoltaic (PV) modules are exposed to high-voltage stress between grounded module frames and solar cells, a configuration called potential-induced degradation (PID). Since PID mainly depends on the solar cells used for module packaging, several steps for PID tests can be omitted. We carried out PID tests on the cell level with Na fault injection in accordance with IEC 62804 and examined the extent of PID with saturation current density ( J 02 ) extracted from I–V measurements in the dark. Na-fault injection is a reasonable means for performing PID tests on the cell level without module packaging. Highlights: We carried out potential induced degradation tests on the cell level with Na fault injection. We extracted J 02 from dark J-V, which was measured at both the cell and module levels. Na fault injection method is a reasonable means of performing PID tests on the cell level.